Analysis of a sprint qualification round in cross-country skiing using a differential global navigation satellite system - Andersson, E.; Supej, M.; Holmberg, H. C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Cross-country (XC) skiing is a sport that comprises many different skiing techniques, between which skiers must continuously swap during a race, depending on the course topography (Holmberg, 2005). In freestyle XC skiing there are five different techniques, called gears (G1-5) (Rapp et al., 2009). A new opportunity for more specific performance analyses of the skier`s speed, accelerations and positions is provided by the Differential Global Navigation Satellite System operating Real Time Kinematic corrections (DGNSS RTK). At present, there are no studies that have analyzed sprint XC skiing in the field combined with the use of video cameras that are synchronized with a DGNSS. The aims of the present study were: 1) to make a descriptive analysis of skiing kinematics, frequency and duration at specific gears during a sprint qualification race in freestyle XC skiing, 2) to evaluate the influence of short sprint (Vmax) abilities versus overall performance in a sprint race. Methods: Nine Swedish male elite XC skiers (four of them top world class skiers), specialized in the sprint or the distance events, volunteered as subjects in the study (mean ± SD: age 25.9 ± 3.5 yr, height 180.7 ± 5.4 cm, weight 74.5 ± 6.2 kg, VO2max 5.5 ± 0.6 l/min and 73.3 ± 5.8 ml/kg/min). The study started with a measurement of the subject`s aerobic capacity in the laboratory, followed by specific sprint tests on snow. These were: 1) two 20-m Vmax tests performed in the G3-technique, 2) two 20-m Vmax tests performed in the double poling (DP) technique and finally 3) an individual race over 1425 m. Results: The mean frequencies at specific gears were: G2 1.02 ± 0.05; G3 0.66 ± 0.04; G4 0.72 ± 0.07; G5 1.07 ± 0.08 Hz. The mean distributions (%) of total race time at specific gears were: G2 16.9 ± 9.3; G3 36.2 ± 7.7; G4 3.2 ± 2.9; G5 18.3 ± 3.2; "G6" (curve technique) 13.1 ± 1.1; "G7" (downhill standing) 9.9 ± 2.2%. There was a significant correlation between DP-Vmax and race time (r = -0.71, P = <0.05). DP-Vmax correlated positively with the skier`s percent of race time at G3 and negatively with the skier`s time at G2 (G2: r = - 0.83, P = <0.05, G3: r = 0.71 P = <0.05). Flying G3-Vmax correlated with the skier`s sprint rank (FIS) (r = - 0.73, P = <0.05). Conclusions The main findings were 1) there was a great range in the choice of skiing technique, G3 or G2, between skiers in the uphill sections, 2) A high Vmax is of importance for success over sprint distances and the DP-Vmax correlations verifies the importance of the upper body in freestyle sprint XC skiing.